2010
DOI: 10.1007/s11251-010-9154-1
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive scaffolding in an innovative learning arrangement

Abstract: This study examined the effects of metacognitive scaffolds on learning outcomes of collaborating students in an innovative learning arrangement. The triads were supported by computerized scaffolds, which were dynamically integrated into the learning process and took a structuring or problematizing form. In an experimental design the two experimental groups receiving scaffolds were compared with a control group. The experimental groups differed in the form of scaffolding used: structuring scaffolds versus probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 27 publications
2
47
2
1
Order By: Relevance
“…The results of this study suggest that providing learners with problematizing scaffolds during learning can effectively improve their self‐regulation and enhance their learning achievements. Structuring scaffolds provide directive guidelines for game design, which may cause students to have difficulty transferring prior knowledge to a new situation (Molenaar et al , , ). Furthermore, the idea at the core of structuring scaffolds is that by providing structure or constraints (in the form of explicit direction or by narrowing choices), the complexity of the task is reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study suggest that providing learners with problematizing scaffolds during learning can effectively improve their self‐regulation and enhance their learning achievements. Structuring scaffolds provide directive guidelines for game design, which may cause students to have difficulty transferring prior knowledge to a new situation (Molenaar et al , , ). Furthermore, the idea at the core of structuring scaffolds is that by providing structure or constraints (in the form of explicit direction or by narrowing choices), the complexity of the task is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…But what would happen if students were provided with problematizing scaffolds instead of structuring? Previous researchers have discovered that students presented with problematizing scaffolds have a higher transfer of domain knowledge than students with structural support (Molenaar, van Boxtel & Sleegers, , , ). The influence of goal specificity is well documented for problem‐solving tasks; however, no empirical studies have been performed to determine how goal specificity is influenced by structuring and/or problematizing scaffolds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies showed that these scaffolds did not affect group performance and did not affect cognition sequences (Molenaar & Chiu, 2014; Molenaar, van Boxtel, & Sleegers, 2011). …”
Section: Methodsmentioning
confidence: 98%
“…Yet, metacognitive activities play an important role in group work as well and these metacognitive skills might need explicit scaffolding as well (cf. AskellWilliams et al 2012;Molenaar et al 2011). Future classroom research should therefore jointly investigate the scaffolding of students' cognitive and metacognitive activities.…”
Section: Limitationsmentioning
confidence: 99%